Reproductive Tract Infections Among Married Women in Peri-Urban Areas of Karachi, Pakistan: A Population-Based Study - Neelofar Sami; Tazeen Saeed Ali; Erum Khan (Medsci Publications, 2013)
Background: Reproductive Tract Infections (RTIs) is a major public health problem. In Pakistan, there is dearth of information about the prevalence of RTIs among women and their health seeking behavior. A study was conducted to determine the prevalence, number and types of RTIs among women residing in squatter settlements in Karachi and their health seeking behavior. Methods: The respondents were married non-pregnant women aged 15-49 years residing in peri-urban areas of Karachi, Pakistan. The interviews with women were followed by their physical and pelvic examinations. Samples swabs collected from vagina and endocervix were tested in laboratory. Results: Overall, 23.8% of the women had laboratory-diagnosed RTIs. Nearly 2.6% had trichomoniasis and 1.7% were positive for syphilis. Bacterial vaginosis was diagnosed in 8.8% and vaginal candidiasis in 13.2 %. Conclusion: The study indicates a high prevalence of RTIs among women with Bacterial vaginosis and trichomoniasis to be the most prevalent endogenous infection and STI respectively. The women considered many symptoms as normal and did not seek treatment. These are the cases that have a potential to remain infected for a long time.